Storytelling in the development communication studies locating the narrative of participation through the interpretive lens - Custodio, Pamela A. (2008)
Researches in development communication are dominated by methodologies situated in the discourse of representation (Mumby, 1997), of the modernist worldview, of determining and measuring effectiveness, of mapping information flows, and of establishing casual and network relationships (Ables, 2003). Studies concerning the notion of participation have been about finding the behavioral variables that contribute to participation in terms of the "seen", i.e., engagement in activities and sharing among stakeholders (Rajan, 1993; Custodio, 1998; Gonzalves, et. al., 2005).

The succeeding discussions attempt to lay down premises that the notion of participation sits in the intersection of the discourses of suspicion and vulnerability (Mumby, 1997), in the traditions of the critical theory and postmodernism. Participation as a concept can be viewed as straddling these two traditions. It was in the works of Paolo Friere and Jurgen Habermas where communication has been identified as intrinsic to social emancipation and empowerment. For Friere, dialogue as intercommunication forms the basis of reflection and action. His ideas were the basis of experiential learning as participatory approach to many adult education and training initiatives for development. Habermas, on the other hand, views "actors in society seeking to reach common understanding and to coordinate actions by reasoned argument, consensus, and cooperation rather than strategic action strictly in pursuit of their own goals (Habermas 1984 p.86 in Bolton 2005). The emerging importance of dialog and communication has been highlighted in the works of organizational communication scholars who have pioneered inquiries into the nature of organizations as constituted in text and conversation (Taylor et. al., in Saludadez 2004). Their modes of inquiry used stories and narratives that privileged communication as a way to explain action and reality (ontology), i.e., the nature of reality is communicatively shaped and that stories are ways to produce and reproduce knowledge.

Further, it hopes to underscore the appropriateness of qualitative approaches in development communication studies particularly in studies aiming to surface underlying assumptions of community process and in giving voice to those less heard.

Surfacing the notions of participation using qualitative and communication lenses entails finding texts within which embedded meanings may be found. One such text is the stories that people who have been engaged in participatory initiatives as well. This paper surveys literature that aims to provide grounding on the legitimacy of the interpretative lens and story analysis as a valid methodology in development communication research.
Keywords: Storytelling